A stylistics analysis of figurative language in Inside Out 2 (2024) - Reva Nita; Wilma Prafitri (Fakultas Ilmu Budaya Universitas Mulawarman, 2026)
This study aimed to explore the use of figurative language in the dialogues of the film Inside Out 2 (2024). The research used a qualitative descriptive method to describe the types of figurative language based on Perrine’s theory. The data consisted of words and phrases found in the dialogues spoken by the two main characters, Joy and Anxiety. The data was collected by repeatedly watching and observing the film, capturing relevant scenes, highlighting dialogues that exhibited figurative language, analyzing and classifying the types of figurative language. The study revealed six types of figurative language: metaphor, apostrophe, synecdoche, metonymy, hyperbole, and irony, with irony appearing as the most frequently type. The findings showed that figurative language in the film functioned not only as a stylistic effect but also as a means to represent emotional complexity in a more concrete and relatable form. By examining the film’s stylistic choices, the study demonstrated how figurative expressions contributed to deeper character portrayal and emotional nuance, especially in reflecting the internal struggles of Riley as she undergoes emotional development. This research contributes to the field of stylistics by illustrating how figurative language can be effectively used in animated films to visualize abstract emotions and enhance audience understanding.